INFLUENCE OF HUMAN RESOURCE COMPETENCY ON THE PERFORMANCE OF THE REGIONAL DISASTER MANAGEMENT AGENCY, POHUWATO REGENCY - Titin Dunggio; Ikram Mohamad; Hartati Hamiruddin (Governance: Jurnal Ilmu Administrasi Publik, 2023)
The purposes of this research are: (1) Analyzing and explaining the Influence of employee’s work knowledge on the Performance of Regional Disaster Management Agency, Pohuwato Regency (2) Analyzing and explaining the Influence of employee’s work skills on the Performance of Regional Disaster Management Agency, Pohuwato Regency, (3) Analyzing and explaining the influence of employee’s work attitude on the Performance of Regional Disaster Management Agency, Pohuwato Regency, (4) Analyzing and explaining the influence of employee’s knowledge, employee’s work skills, and employee’s work attitude on the Performance of Regional Disaster, Pohuwato Regency.